Some Sharp Results on Coefficient Estimate Problems for Four-Leaf-Type Bounded Turning Functions - Pongsakorn Sunthrayuth; Yousef Jawarneh; Muhammad Naeem; Naveed Iqbal; Jeevan Kafle (Journal of Function Spaces)
In this study, we focused on a subclass of bounded turning functions that are linked with a four-leaf-type domain. The primary goal of this study is to explore the limits of the first four initial coefficients, the Fekete-Szegö type inequality, the Zalcman inequality, the Kruskal inequality, and the estimation of the second-order Hankel determinant for functions in this class. All of the obtained findings have been sharp.